2023
DOI: 10.1136/bmjdrc-2022-003205
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity, SNAP participation and glycemic control in low-income adults with predominantly type 2 diabetes: a cross-sectional analysis using NHANES 2007–2018 data

Abstract: IntroductionDiabetes, characterized by elevated blood glucose levels, affects 13% of US adults, 95% of whom have type 2 diabetes (T2D). Social determinants of health (SDoH), such as food insecurity, are integral to glycemic control. The Supplemental Nutrition Assistance Program (SNAP) aims to reduce food insecurity, but it is not clear how this affects glycemic control in T2D. This study investigated the associations between food insecurity and other SDoH and glycemic control and the role of SNAP participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Numerous retrospective, epidemiologic studies have shown an association between SDoH and overweight/obesity, diabetes, hypertension and hyperlipidemia (61)(62)(63)(64)(65)(66). These studies often use national databases that collect data on social factors via surveys or link census data by geographic location and use area or neighborhood deprivation indices.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous retrospective, epidemiologic studies have shown an association between SDoH and overweight/obesity, diabetes, hypertension and hyperlipidemia (61)(62)(63)(64)(65)(66). These studies often use national databases that collect data on social factors via surveys or link census data by geographic location and use area or neighborhood deprivation indices.…”
Section: Discussionmentioning
confidence: 99%